Heme Oxygenase-1 Attenuates Hypoxia-Induced sFlt-1 and Oxidative Stress in Placental Villi through Its Metabolic Products CO and Bilirubin - George, Eric M. (Hindawi Publishing Corporation, 2012)
One of the most prevalent complications of pregnancy is preeclampsia, a hypertensive disorder which is a leading cause of maternal and perinatal morbidity and premature birth with no effective pharmacological intervention. While the underlying cause is unclear, it is believed that placental ischemia/hypoxia induces the release of factors into the maternal vasculature and lead to widespread maternal endothelial dysfunction. Recently, HO-1 has been shown to downregulate two of these factors, reactive oxygen species and sFlt-1, and we have reported that HO-1 induction attenuates many of the pathological factors of placental ischemia experimentally. Here, we have examined the direct effect of HO-1 and its bioactive metabolites on hypoxia-induced changes in superoxide and sFlt-1 in placental vascular explants and showed that HO-1 and its metabolites attenuate the production of both factors in this system. These findings suggest that the HO-1 pathway may be a promising therapeutic approach for the treatment of preeclampsia.